Integrated Marketing Communication Strategy of PT. Syngenta Indonesia in Increasing Corn Farming Productivity Through the Use of Digital Technology for PeTani Apps - Rahmi Lutfial Umi, Anisa; Hasanah Sudradjat, Ratih (PT Mattawang Mediatama Solution, 2024)
The emergence of the peTani Apps represents PT. Syngenta Indonesia’s innovative response to enhancing corn farming productivity through digital technology utilization. In 2023, the user base of the peTani Apps reached 28,600, a significant increase from the previous year. This research aims to examine the integrated marketing communication (IMC) process undertaken by PT. Syngenta Indonesia in boosting corn farming productivity through digital technology, particularly via the peTani Apps, employing Kotler and Keller's (2016) IMC strategy concept. The research method employed is qualitative descriptive with a post-positivist paradigm and data triangulation method. The findings reveal that PT. Syngenta Indonesia effectively implements IMC strategy to enhance corn farming productivity through the peTani Apps. The company has conducted extensive promotional efforts through various online news portals and social media, alongside sales promotion programs offering discounts and special deals. Through participation in agricultural events and collaboration with stakeholders, the company has expanded reach and heightened awareness of the application. Support is also provided through direct marketing, digital marketing focus, and the use of specialized teams for farmer education